Volcano geo facts - Howell, Izzi (Geofacts (Crabtree Publishing Company), 2018)
Examines the geographical science behind volcanos, including where and how they form, their power to change the landscape and atmosphere, and notable volcanos in history. Includes a glossary, text-related questions with an answer key, resources for further information, diagrams, maps, and color photographs.